2015
DOI: 10.1021/jp509879v
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigation into the Light Soaking Effect Observed in Inverted Polymer Solar Cells Containing Chemical Bath Deposited Titanium Oxide

Abstract: In the glass-indium tin oxide (ITO) / titanium oxide (TiO x ) / regioregular poly(3-hexylthiophene) (P3HT) : [6,6]-phenyl C 61 butyric acid methyl ester (PCBM) / poly(3,4-ethylenedioxylenethiophene) : poly(4-styrene sulfonic acid) (PEDOT:PSS) / Au cell (TiO x cell), which contains amorphous titanium oxide prepared by chemical bath deposition and dried at 150 °C, a light soaking effect has been observed upon irradiation with white light.In contrast, in ITO / titanium oxide (TiO 2 ) / P3HT:PCBM / PEDOT:PSS / Au … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 29 publications
(72 reference statements)
2
26
0
Order By: Relevance
“…[3][4][5][6][7] One of the fundamental issues is the light-soaking phenomenon with respect to UV-light irradiation, which has been commonly observed in IOSCs with electron-collecting layers such as TiO x . 2,[8][9][10][11][12][13][14][15] Although high-temperature annealing treatments on the TiO x layer can prevent the phenomenon, such treatments are undesirable for low-temperature device fabrication using flexible plastic substrates. 15 Additionally, long-term UV-light irradiation on IOSCs can cause device degradation.…”
mentioning
confidence: 99%
“…[3][4][5][6][7] One of the fundamental issues is the light-soaking phenomenon with respect to UV-light irradiation, which has been commonly observed in IOSCs with electron-collecting layers such as TiO x . 2,[8][9][10][11][12][13][14][15] Although high-temperature annealing treatments on the TiO x layer can prevent the phenomenon, such treatments are undesirable for low-temperature device fabrication using flexible plastic substrates. 15 Additionally, long-term UV-light irradiation on IOSCs can cause device degradation.…”
mentioning
confidence: 99%
“…19,22 On the other hand, the trap states, close to the ZnO/P3HT:PCBM, could change the induced interfacial dipoles. 23,24 Presented data do not consider which interface (ITO/ZnO or ZnO/P3HT:PCBM) plays the key role in the lightsoaking effect but highlight the need for taking into account the LS effect in the analysis. The impact of light-soaking effect is increasing in time and it should be considered for proper and reliable measurements and stability analysis.…”
Section: Changes In Magnitude Of the Light-soaking Effect During The mentioning
confidence: 99%
“…19,22 In the second case, the key role in the light-soaking effect plays the interfacial dipole between the metal-oxide/organic interface. [23][24][25] Sometimes the devices should be stimulated under solar simulator for at least few minutes (∼10 min) at the 1000-W∕m 2 illumination intensity, for saturation of their photovoltaic properties. For the outdoor application, this illumination time could be equal to 1 to 2 h per day due to much lower solar irradiation intensity each morning.…”
Section: Introductionmentioning
confidence: 99%
“…However, such the increasing process is poorly understood, although several mechanisms have been suggested. [11][12][13][14][15] We previously have found that there are two kinds of light soaking effects such as a short-circuit current density (J sc ) dependent type [16][17][18] and an open-circuit voltage (V oc ) dependent type 19 as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…We had also investigated the mechanism of the both lightsoaking effect observed in the polymer solar cells using both ac impedance spectroscopic (IS) and electron spin resonance (ESR) measurements. 17,18,20 We have found that these light soaking effects are caused by favorable charge accumulations for suppressing the recombination and disappearing the charge-injection barrier between the electron collection electrode and the organic active layer. The expression of the effects needs to excite the electron collection layer such as n-type semi-conductive metal oxide by UV-light irradiation.…”
Section: Introductionmentioning
confidence: 99%